15th World Congress on Gastrointestinal Cancer - Oblak, Irena; Potrč, Stojan (Onkologija : Slovenian Journal of Oncology, 2013)
The 15th World Congress on Gastrointestinal Cancer took place from 3 to 6 July 2013 in Barcelona. This is a global event addressing individual types of gastrointestinal cancer in accordance with the latest recommendations and findings, from diagnosis to treatment. The focus is on individual management of each patient and the importance of a multidisciplinary approach, including the most recently discovered molecular mechanisms. Over 60 world-renowned lecturers, all experts in their fields, presented the latest findings and recommendations or lead small targeted groups of physicians who attended sessions on specific topics. At the Congress, the participants were also given the opportunity to present their research results, with their abstracts being published in the Annals of Oncology. Two Slovenian abstracts were presented, both from the field of postsurgical treatment of gastric cancer. In the following pages, we will present only some of the new findings and the outlines presented at the Congress.